Jaunissement Mortel du Cocotier et Mutations Sociales à Grand-Lahou, Côte d’Ivoire - N’guessan, Tenguel Sosthène; Kouame, Daniel Kra; Ibo, Guéhi Jonas; Taky, Hortense Atta Diallo (European Scientific Journal, ESJ, 2019)
Coconut farming is an important part of the Ivorian economy and governs the lives of people who grow it. However, the Lethal Yellowing Disease (LYD), occurring in the Ivoirian plantations of Grand-Lahou has undermined the foundations of the social economy and the social dynamics by their perverse effects. In order to identify the social implications of the fatal yellowing of the coconut tree, a study was conducted in ten villages in GrandLahou subject to this epidemic. The collection of quantitative data was carried out among 101 people determined by quota sampling. Qualitative survey was conducted among 10 women and 10 men all involved in the production and processing of coconut. For data managment, S.P.S.S for quantitative data and MaxQDA for qualitative data were used. The results attest to the respondents’ sufficient life experience to appreciate the impact of the LYD. The consequences of the Lethal Yellowing Disease relate to the disruption of the traditional customary designation system (81.8%), the lack of local development resulting from the loss of income (15.8%) and areas of plantation plantations (83.2%), the relaxation of intergenerational relations between seniors and cadets. Despite its weak impact on polygamy as a cultural construct, the LYD participates in the transformation of gender relations which promote women’s access to land and their autonomy. Ultimately, the JMC is presented as a social fact participating in the development of women but laying the foundation for a weakening of the collective consciousness. La culture du coco constitue un pan important de l’économie ivoirienne et régente la vie des populations qui la cultivent. Cependant le jaunissement mortel du cocotier (JMC), intervenu dans les plantations ivoiriennes de Grand-Lahou a sapé les fondements de l’économie sociale et la dynamique sociale par leurs effets pervers. Afin de cerner les implications sociales du jaunissement mortel du cocotier, une étude a été conduite dans une dizaine de villages de Grand-Lahou sujets à cette épidémie. La collecte de données quantitatives a été effectuée auprès de 101 personnes déterminées par l’échantillonnage par quotas. Celles qualitatives ont été réalisées auprès de 10 femmes et 10 hommes tous impliqués dans la production et la transformation de la noix de coco. Pour le traitement et l’analyse des données quantitatives, il a été mobilisé le logiciel Statistical Package for Social Sciences (S.P.S.S) tandis que l’usage de MaxQDA a été fait pour les données qualitatives. Les résultats attestent d’une espérance de vie suffisante des répondants pour apprécier l’impact du JMC. Les implications du jaunissement mortel du cocotier portent sur le bouleversement du système traditionnel de désignation de l’autorité coutumière (81,8%), l’absence de développement locale conséquence de la perte de revenus (15,8%) et des superficies de cocoteraies (83,2%), ainsi que le relâchement des relations intergénérationnelles aînéscadets. Malgré son faible impact sur la polygamie comme construit culturel, le JMC participe à la transformation des relations de genre favorisant l’accès de la femme à la terre et son autonomie. En définitive, le JMC se présente comme un fait social participant à l’essor de la femme mais jetant les jalons d’un affaiblissement de la conscience collective.